Macedonia Towards EU Integration, In Front of Challenges of Economic Development - Dr. Harun Tairi; Mr. Xhejnet Osmani; Mr. Skender Arifi (Research Parks Publishers, 2022)
Macedonia and its integration into the EU has a difficult road ahead of it, but even this time it will succeed when we compare the difficulties it went through. Once again, it will affirm its right and live equally with all the peoples of the Balkans and beyond. Macedonia's era of independence is characterized by reforms in education, health, trade, state administration, executive, legislature and judiciary, etc. Regional cooperation is a central element of the European Union's efforts to advance the reform process in the Western Balkan countries and to help the region achieve economic prosperity and political stability. In this paper, a special place is occupied by international trade, which is realized mainly in the currencies of large economies that are widely accepted as international means of payment, so Macedonia will pay attention to the economic development of the country. Other problems plaguing developing countries and Macedonia include volatile export markets, deteriorating trade conditions and limited access to markets in industrialized countries. In general, the paper addresses many areas that Macedonia needs to consider in order to integrate into the structures of the European Union. However, the pace, dimensions and scope of Macedonia's EU integration reforms are now addressed by the country's political elite, democratic institutions and its citizens.